MMCT energy change in cyanidometal-bridged trinuclear complexes by changing the ligand electron donating ability. (23rd March 2023) - Qian, Wang; Liu, Xiao-Lin; Tan, Bing-Chang; Song, Ying; Jiang, Long-Long; Wu, Xin-Tao; Sheng, Tian-Lu
Abstract : To investigate the effect of MMCT in the complexes of cyanidometal-bridges, we synthesized and fully characterized a series of N 2+ ( N = 1, 2, 3, 4, 5), and their one and two-electron oxidized products N 3+ and N 4+ are Class II mixed-valence compounds. Abstract : To investigate the effect of metal-to-metal charge transfer (MMCT) in the complexes of cyanidometal-bridges, we synthesized and fully characterized a series of trimetallic cyanidometal-bridged compounds with the formula trans-[CpMe x Fe–NC–Ru(L)4 –CN–FeCpMe x ][PF6 ]2, N 2+ [PF6 ]2 (L = i-PrPy, N = 1, x = 0; N = 2, x = 1; N = 3, x = 3; N = 4, x = 4; N = 5, x = 5), and their one-electron and two-electron oxidized products N 3+ [PF6 ]3 and N 4+ [PF6 ]4 . Electrochemical measurements show the presence of electronic interactions between the two terminal Fe units. As methyl substituents on the Cp ligands increase, the change trend of the MMCT energy from the remote terminal Fe II to Fe III in complexes N 3+ is not obvious, which may be due to the increase in the electron-donating ability of the Cp ligands on both the terminals, electron-donating Fe II and electron-accepting Fe III ions, while the MMCT energy from the neighboring Ru II to the terminal Fe III in complexes N 4+ decreases, strongly supported by the TDDFT calculations. All the mixed-valence compounds N 3+ and N 4+ belong to Class II systems.